Pengaruh Modal Kerja, Hutang, Dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Sektor Keuangan Yang Terdaftar Di BEI Tahun 2019-2021 - Fahmi Utaminingsih; Listyorini Wahyu Widati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this research is to find out the actual situation of the impact of working capital, debt and liquidity on profitability simultaneously or partially, by using working capital, debt and liquidity as independent variables, profitability as the dependent variable. This research uses data sourced from the financial reports of financial sector companies starting from 2019-2021. The total number of financial companies listed on the IDX is 105 companies and 103 companies are included in the test criteria, with an initial sample of 360 samples consisting of 103 companies multiplied by three years, then after being tested for normality there are extreme data, so the data is outlier so that the sample becomes 91. In this study using SPSS software version 24. The results of the study show that the working capital variable has a negative and insignificant effect on profitability. The debt variable has a negative and significant effect on profitability. The liquidity variable has a positive and significant effect on profitability. The results of testing the working capital hypothesis on profitability obtained 0.807. Testing the debt hypothesis on profitability obtained 0.04 however, while testing the liquidity hypothesis obtained 0.01Keywords : Working Capital, Leverage, Liquidity, Profitability